Anterior–posterior topographic patterns of thoracic joint structural abnormalities on chest CT in psoriatic arthritis - Rui Li; Hui Sang; Yuxiang Zhang; Yong Wang; Yu Gao; Jianzhao Wang; Xiaomeng Qin; Yanfang Song; Tianshu Li (Frontiers in Medicine, 2026)
Objective This study sought to develop and evaluate a chest computed tomography (CT)-based thoracic ring topographic framework for characterizing the anterior–posterior distribution of structural involvement in patients with psoriatic arthritis (PsA). Methods This retrospective study included 279 patients with PsA who underwent clinically indicated chest CT. The sternoclavicular joint (SCJ), costovertebral joint (CVJ), and costotransverse joint (CTJ) were assessed. A compartment was considered positive when its structural burden score exceeded 0 or any prespecified structural feature was present. Patients were classified as anterior–posterior (A–P) ring, posterior-only, negative, or anterior-only phenotypes. Results SCJ, CVJ, and CTJ positivity occurred in 131 (47.0%), 232 (83.2%), and 236 (84.6%) patients, respectively. All SCJ-positive patients were also positive at both posterior compartments, and no anterior-only phenotype was observed. The A–P ring, posterior-only, and negative groups comprised 131 (47.0%), 111 (39.8%), and 37 (13.3%) patients. Median total structural burden was 59.0, 40.0, and 0.0, respectively ( P < 0.001). After adjustment, A–P ring involvement was associated with higher total burden than posterior-only involvement ( β = 7.98, 95% CI: 3.42–12.54; P < 0.001), whereas the adjusted difference in posterior burden was not statistically significant ( β = 4.45, 95% CI: −0.06 to 8.97; P = 0.053). Conclusion SCJ positivity occurred within a combined anterior–posterior pattern and was associated with greater overall structural burden. Thoracic ring topography may provide a spatial framework that requires independent and multimodal validation.